2006
DOI: 10.1007/s10519-006-9097-0
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Drug Self-administration in Mice: Practical Considerations

Abstract: Chronic intravenous drug self-administration in rodents is a useful procedure for predicting the abuse liability of novel drugs in humans, for evaluating candidate treatments for drug abuse and dependence, and for studying the biological basis of addiction. Despite the technical challenge in achieving chronic self-administration behavior in the mouse species, researchers are increasingly using genetically engineered mice to investigate the role of specific genes in abuse-related effects of drugs. This review f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 79 publications
2
53
0
Order By: Relevance
“…2). Previous studies have demonstrated a plateau in responses by C57BL/6 mice at 1.0 mg/kg/infusion (Thomsen and Caine, 2007), and our data concur (Supplemental Fig. 2).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…2). Previous studies have demonstrated a plateau in responses by C57BL/6 mice at 1.0 mg/kg/infusion (Thomsen and Caine, 2007), and our data concur (Supplemental Fig. 2).…”
Section: Discussionsupporting
confidence: 90%
“…The animals that were trained at the 1.0-mg/kg dose then went on to a 1-day progressive ratio task, which also demonstrated no genotypic difference in the number of infusions earned (graph not shown: Wt 6.92 6 1.4; Kal7 KO 5.49 6 1.3; results of a two-tailed t test showed t 5 0.78, df 5 51, P 5 0.44). Higher doses of cocaine per infusion were not tested, as previous studies have shown 1.0 mg/kg to be the dose at which C57/bl6 mice typically plateau (Thomsen and Caine, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…First is the use of freefed mice. Food restriction is a common strategy to increases rodents' operant responding in self-administration procedures (Caine et al, 1993;Elmer et al, 1986;Hayward et al, 2004;Heidbreder et al, 2007;Nguyen et al, 2005;Middaugh et al, 1999;Thomsen and Caine, 2007). However, the fact that this can alter the neurochemical pathways mediating drug-reinforcing properties is often overlooked: a 20-50% decrease in extracellular dopamine (DA) levels was observed in the nucleus accumbens (NAc) of food-restricted rats (Pothos et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…These behaviours are known to differentially rely on dopamine signalling [134,202,203] and predict different forms of relapse [150,204,205]. Drug self-administration studies using intravenous catheters [206] and certain impulsivity tasks [207,208] are also much more challenging to conduct in mice. Additionally, some behaviours believed to serve as particularly useful models of human relapse and addiction, including compulsive cocaine seeking in the face of punishment [209], are unexplored in mice.…”
Section: (B) Conceptual Limitationsmentioning
confidence: 99%